Peningkatan Kompetensi Akuntansi Melalui Pemanfaatan Aplikasi Pada Smartphone - Susilawati, Susi; Samukri; Saleh, Ridwan; Yuli, Rama; Suryaningsih, Maria; Pratami, Shalsa Dita; Suwandi, Lisa Fitria (PASAI : Jurnal Pengabdian kepada Masyarakat, 2023)
The need for the Internet is not only as a medium for entertainment or viewing but also for many others, including helping to prepare financial performance reports for business activities. Therefore, there is a need for understanding and knowledge for the public, especially young people who are learning to do business, so they no longer think that software or applications for financial reporting must be obtained difficultly and expensively. Still, it can also be obtained through other means like a smartphone at a low cost or even free. The method used in implementing community service is training through presentations delivered by community service team presenters, and practice using applications via smartphone. The discussion presented is 1) the history of the accounting recording process up to the use of applications available on computers or smartphones, and 2) introducing the application and providing training on accounting recording through the SIAPIK application. With this training, it is hoped that Binar High School students can increase their knowledge and competence in using simple accounting applications based on Android (via Playstore) and IOS.